2015
DOI: 10.1002/jib.254
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of total polyphenols, bitterness and haze in pale and dark lager beers produced under different mashing and boiling conditions

Abstract: *Malting and brewing processes should be performed under process conditions in a way that minimizes beer bitterness, maximizes polyphenol content and reduces the amount of raw materials ending up in solution in the form of hazes, particles and precipitates. This work examined the influence of different mashing temperature conditions and boiling procedures on the total polyphenol content, bitterness and haze of pale and dark lager beers produced on an industrial scale. Two hop types (hop pellets and/or hop extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
5
15
0
Order By: Relevance
“…The amount of TPC variation comes from the difference in raw material used mainly from malt and hope and the nature of beer production process [20,21]. The results obtained in this study were in agreement with reported values [1,5,6,20]. So, the difference in amount of total polyphenols can cause difference on their antioxidant activities, avour, color and sensory properties and also may contribute to maintain the endogenous redox balance in humans [9].…”
Section: Total Polyphenols Contentsupporting
confidence: 85%
“…The amount of TPC variation comes from the difference in raw material used mainly from malt and hope and the nature of beer production process [20,21]. The results obtained in this study were in agreement with reported values [1,5,6,20]. So, the difference in amount of total polyphenols can cause difference on their antioxidant activities, avour, color and sensory properties and also may contribute to maintain the endogenous redox balance in humans [9].…”
Section: Total Polyphenols Contentsupporting
confidence: 85%
“…Investigating the Brazilian beers, we found that the contents of phenolic compounds, as well as the antioxidant capacity, were like those of beers produced elsewhere in the world [2]. Polyphenols are already extracted in the initial phase of the fermentation process, i.e., during the wort production [9]. This study showed that polyphenols, especially the bitterness associated with it, have an important relationship with the preference of different beers among Brazilian consumers.…”
Section: Discussionmentioning
confidence: 58%
“…In this sense, an extensive study was carried out by Zhao et al in 2010 [47], in which 34 lager beers were analyzed and where TPC ranged between 152 and 339 mg GAE/L. Other later studies on Polish, Belgian, Serbian, Indian or Hungarian beers agree with that study [60,66,72,74,75] In general, ale beers present higher TPC than lagers [76]. In a comparative study between different Brazilian beers, it was observed that brown ale beers presented higher TPC than lager beers and also higher antioxidant properties [69].…”
Section: Total Phenolic Content Measurementmentioning
confidence: 67%